OPTIMASI WAKTU EKSEKUSI PENENTUAN RUTE MENUJU OBYEK WISATA DI MALANG RAYA DENGAN ALGORITMA GENETIKA - Yunus, Mahmud; Rumlaklak, Ryan Markus Thobias (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
As one of the tourist destinations in Indonesia, the area of Malang Raya offers a variety of interestingtourist attractions. Based on BPS statistics from Kota Batu in 2015, total tourist visits were 2,089,022people. While the total tourist visit in 2014 in Malang Regency is 2,118,008 people. Data was taken at22 tourism object in Batu Town and 10 tourism object in Malang Regency. The location of thedestination of several distant attractions, a constraint for tourists to determine the optimal route to thetourist attraction. One alternative solution to the problem can be done using Genetic Algorithms. Thefocus of this research is to build a web based application that can provide information on the order ofroute of visits to some tourism objects optimally. Implementation is done based on the completion ofTraveling Salesman Problem, using Genetic Algorithm method. Variable optimization is (1) theshortest total distance; and (2) application execution time with Brute Force algorithm as acomparison. The results show that if the location of the chosen destination is numerous, the GeneticAlgorithm is more efficient in the use of time and resources than the Brute Force algorithm.